On the Estimation of the Rate of Convergence in the Multi-dimensional Central Limit Theorem. I - Paulauskas, V. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Паулаускас. Об оценке скорости сходимости в многомерной центральной предельной теореме. IV. Paulauskas. Apie konvergavimo greičio įvertinimą daugiamatėje centrinėje ribinėje teoremoje. I